Synchronization between Indonesia and Balinese Village Law (A Community Social Service at Peninjoan Village, Tembuku Districts, Bangli Regency, Bali) - I Putu Sastra Wibawa; Ida Bagus Alit Yoga Maheswara; I Made Dwija Suastana; Made Gede Artadana; Komang Indra Apsaridewi (Fakultas Hukum, Universitas Warmadewa, 2022)
In the legal system of the unitary state of the Republic of Indonesia, there is a hierarchy of laws and regulations that must be obeyed by all citizens. Since Indonesia’s independence in 1945, efforts have been made to promulgate various legal regulations down to the lowest level, namely in the villages. It must be admitted, these efforts are still being carried out by the government to this day. Scholars through their tri dharma program, namely community social service, also participate in assisting the government in providing enlightenment in the field of legislation to rural communities. Traditional village governance and traditional villages have existed long before Indonesia’s independence. For this reason, continuous efforts are needed to synchronize the various existing regulatory instruments in order to create harmony in law and government in Indonesia. This is an imperative action taken by the scholars in order to strengthen the participation of the communities in the law enforcements administratevily to achieve the goal of practical sustainable law enforcement. The approach method used in this research is the statute approach, the comparative approach, and the analytical and concept approach. The aims of this research is to synchronize national regulations with regulations at the village level, especially in Peninjoan Village.